Application of FEMA and RPN techniques for man-machine analysis in Tobacco Company. Issue 1 (1st January 2019) - Ostadi, Bakhtiar; Masouleh, Mehrdad Saboory
Abstract: With the rapid growth of the industries and commercial space being more competitive attention to quality control and most importantly to produce zero defect products has become more important than ever. Retaining customers, attracting new customers, and making them loyal require many efforts among which producing competitive, high quality, and zero defects products enjoys the highest weight. Recognition of errors and defects in production lines which cause reduction in product quality is an effective lever to eliminate errors and improve the existing situation. In this paper, failure modes and effects analysis (FMEA) technique has been utilized to find errors and their causes in the production line of the Iranian Tobacco Company. With the completion of FMEA table and calculating Risk Priority Number (RPN) values, all errors were zoned and prioritized. The prioritization of the discovered errors based on FMEA technique indicated human error as the most important factor in the emergence of errors.